Upaya Meningkatkan Hasil Belajar Pendidikan Agama Islam Peserta Didik Menggunakan Model Pembelajaran Problem Based Learning pada Kelas X E SMA N 1 Sutera Tahun Pelajaran 2024/2025 - Yerni, Nela (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research is motivated by issues in Islamic Religious Education learning in class X E at SMA N 1 Sutera, where students have not optimally absorbed the lesson material, affecting their learning outcomes. The study aims to improve the learning outcomes of Islamic Religious Education students through learning using the Problem-Based Learning model in class X E SMA N 1 Sutera during the even semester of the 2024/2025 academic year. The research method used is classroom action research, conducted in two cycles. Data collection techniques include tests and observations. The research results show an improvement in students' learning outcomes from cycle I to cycle II.